Gurus and oracles : the marketing of information - Sarvary, M. (Miklos) (MIT Press, 2012)
In this work, Miklos Sarvary describes the information industry - the far-flung universe of companies whose core business is to sell information to decision makers. Sarvary highlights the special characteristics of information and knowledge and analyzes the unusual behaviours of the markets for them.